The Lived Experience of Resilience in Parents of Children With Cancer: A Phenomenological Study - Luo, Yuanhui; Li, Ho Cheung William; Xia, Wei; Cheung, Ankie Tan; Ho, Laurie Long Kwan; Chung, Joyce Oi Kwan (Frontiers in Pediatrics, 2022)
Background Resilience is vital in parents of children with cancer as it can promote parental well-being and minimise maladaptation in the face of the children’s cancer. Although existing quantitative studies investigated the influence factors of resilience in the parents, it has not been fully explored about the factors contributing to the resilience of parents and how they respond to and cope with their children’s cancer. Objective To investigate the lived experience of resilience in the parents of children with cancer from a qualitative perspective to complement existing findings in quantitative studies. Methods A phenomenological approach was used. Purposive sampling was performed to recruit parents of children with cancer from two tertiary hospitals in mainland China, followed by one-to-one semi-structured interviews. All of the interviews were audio-recorded and data were analysed using thematic analysis. Results Twenty-three parents, comprising 15 mothers and 8 fathers, of children with cancer participated in the interview. Four themes were identified: positive and negative experiences of their children’s disease, going through hardships, perceived competence and perceived social support. The most prominent facilitating factor of resilience was the presence of positive attitudes toward the children’s cancer, while low level of confidence was the main obstacle. Conclusion This study identified certain factors that affect resilience in parents of children with cancer. The findings of this study provide important implications for the development of targeted resilience training programs to enhance resilience in parents of children with cancer. It is crucial for future interventions to focus on cultivating parental resilience to promote parents’ mental well-being and improve their quality of life.